Utveckling av ergonomiskt styrdon för CAD-konstruktörer - Firek, Karolina; Savervall, Alfred (My University, 2019)
ABSTRACT Work-related diseases are growing in society, where sedentary is central. Hand movement also affects the body, for instance when working with computer mice or keyboards, which can cause pain in hand, wrist, arm, shoulder and neck. By developing a computer mouse that decreases strain for a large group of users, knowledge can be gathered about a more sustainable working environment and diseases can be decreased or prevented. Ergonomics and function have been explored through interviews, theoretical studies and market analysis. The theoretical studies showed that an important principle to follow when developing ergonomic products is that the body should be as close to its neutral position as possible, i.e. standing up with the arms along the sides. The further away from this position, the greater the risk for injuries to occur. The interviews and market analysis showed that the size of the control tool determined how the comfort was perceived and that the grip varied from person to person. In addition to that, some people thought the buttons on existing computer mice were confusing. The findings were used in different methods to generate solutions, which were screened with certain criteria until six concepts remained. These concepts were made into clay models at an early stage to have their ergonomics tested, where the goal was to reach a high level of comfort and allow the hand to be close to its neutral position. After evaluation, two concepts were picked as the most suitable and were tested by different people. The concept that was best received from users was developed further into four concepts in clay, which optimized ergonomics, function, adaptation for production and aesthetics. These four variants were tested by people with different hand sizes and were ranked according to perceived comfort. The concept with the highest score got a high score from all the participants, which means the concept offers comfort for different hand sizes as well as a relatively neutral hand position. The concept was then constructed in CAD and production requirements was taken into consideration, where after the concept was 3D printed and tested by users. The users stated that the computer mouse fit the hand and felt comfortable. All participants stated that they would consider using the computer mouse as their primary mouse at work. At the same time, the concept is adapted for recycling, which means that no glue is used, few screws are used and only one material is used for the plastic parts. The project did not include analysis of long-term use nor the electronics of the control tool, which is the next step of the product development.
Keywords: Produktion; Innovation och entreprenörskap (nyttiggörande); Annan teknik; Production; Innovation & Entrepreneurship; Other Engineering and Technologies